2023
DOI: 10.3346/jkms.2023.38.e162
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model for Osteoporosis Risk Using a Machine-Learning Approach and Its Validation in a Large Cohort

Abstract: Background Osteoporosis develops in the elderly due to decreased bone mineral density (BMD), potentially increasing bone fracture risk. However, the BMD is not regularly measured in a clinical setting. This study aimed to develop a good prediction model for the osteoporosis risk using a machine learning (ML) approach in adults over 40 years in the Ansan/Anseong cohort and the association of predicted osteoporosis risk with a fracture in the Health Examinees (HEXA) cohort. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
(55 reference statements)
0
5
0
Order By: Relevance
“… 51 , 52 Currently, ML is used in clinical diagnosis and outcome prediction in many medical fields. 53 , 54 , 55 The diagnostic criteria for IVIG resistance in KD are based on clinical parameters, and while traditional predictive models can incorporate only a small number of clinical features, models computed by ML can integrate all aspects of clinical indicators, including continuous variables, without the need for categorization. Additionally, ML models can encompass a wider array of predictors, such as genetic expression, enhancing their predictive capacity.…”
Section: Discussionmentioning
confidence: 99%
“… 51 , 52 Currently, ML is used in clinical diagnosis and outcome prediction in many medical fields. 53 , 54 , 55 The diagnostic criteria for IVIG resistance in KD are based on clinical parameters, and while traditional predictive models can incorporate only a small number of clinical features, models computed by ML can integrate all aspects of clinical indicators, including continuous variables, without the need for categorization. Additionally, ML models can encompass a wider array of predictors, such as genetic expression, enhancing their predictive capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Xuangao Wu and Sunmin Park employed ML approach to develop predictive models for osteoporosis diagnosis using clinical data. Their study demonstrated the utility of ML techniques in accurately classifying individuals with osteoporosis based on a combination of risk factors [19].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have employed a variety of ML techniques such as logistic regression, XGBoost, random forest, K-nearest neighbor, support vector machine, decision trees, and neural networks. These methods address various facets of osteoporosis from risk prediction and early detection to diagnosis, treatment, and management [ 19 23 ].…”
Section: Introductionmentioning
confidence: 99%